2009
DOI: 10.1007/s10658-009-9460-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation and histological changes in muskmelon and autumn squash tissues infected by Acremonium cucurbitacearum or Monosporascus cannonballus

Abstract: Muskmelon (Cucumis melo cv. Temprano Rochet) and autumn squash (Cucurbita maxima) seedlings were inoculated either with Acremonium cucurbitacearum or Monosporascus cannonballus, two of the soil-borne fungi implicated in 'melon collapse'. Inoculation was achieved in two different ways: by growing the plants in pots containing infested soil to study the histological changes produced in the infected tissues using light microscopy and by growing seedlings in Petri dishes together with fungal colonies in order to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Our results of the varietal sensitivity study of C. sativus to P. melonis strain 502 are in agreement with the studies of American and Spanish isolates of P. melonis, which state that the pathogen brings the worst damage to plant roots in the initial stages of growth and development (Alfaro-Fernández and García-Luis, 2009;Biernaki and Bruton, 2001). Young sprouts have a low resistance to the infection, since some mechanisms, present in plants on later stages of development, are absent from their recently formed tissues (Alfaro-Fernández and García-Luis, 2009;Bruton et al, 2000b). Previously we have demonstrated that the plants of Nizhynskyi 12 variety are susceptible on the stage of two actual leaves (after two weeks of growing plants on the AIB of P. melonis 502) (Kopilov et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Our results of the varietal sensitivity study of C. sativus to P. melonis strain 502 are in agreement with the studies of American and Spanish isolates of P. melonis, which state that the pathogen brings the worst damage to plant roots in the initial stages of growth and development (Alfaro-Fernández and García-Luis, 2009;Biernaki and Bruton, 2001). Young sprouts have a low resistance to the infection, since some mechanisms, present in plants on later stages of development, are absent from their recently formed tissues (Alfaro-Fernández and García-Luis, 2009;Bruton et al, 2000b). Previously we have demonstrated that the plants of Nizhynskyi 12 variety are susceptible on the stage of two actual leaves (after two weeks of growing plants on the AIB of P. melonis 502) (Kopilov et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…However, most studies have used Fusarium oxysporum and other crops in the Cucumis genus [9,10], while molecular studies of Phytophthora capsici have used horticultural crops such as pepper [11,12]. Many of the plant defensive tools against soilborne pathogenic fungi are enzymes that act directly on pathogens, such as chitinases, 1,3-glucanases/glucosidases, and peroxidases [13][14][15]; are involved in the production of defense structures such as lignin [16], tylose [17], and suberin [18]; are antimicrobial molecules (phytoalexins) [19]; or are oligopeptides (defensins) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the specificity of M. cannonballus showed that germination of ascospores is extremely host specific and occurs only in the rhizosphere of certain genera and species of plants belonging exclusively to the Cucurbitaceae family [4]. In a histological study using artificial inoculation with active mycelium, Alfaro-Fernandez and García-Luis [5] examined the early colonization of M. cannonballus in two cucurbit species that differed in their sensitivity to this disease: a highly sensitive muskmelon ( C. melo ) and a tolerant squash ( Cucurbita maxima ). Results showed that M. cannonballus was capable of infecting the tissue of both host plants, colonizing the epidermis and cortex with decreased density of mycelium at the endodermis level.…”
Section: Introductionmentioning
confidence: 99%